EFFECT OF PAYABLE TO PROFITABILITY IN SECTOR COMPANY INFRASTRUCTURE, UTILITIES, AND TRANSPORTATION IN IDX PERIOD 2010 - 2014 - Yohan Prasetyo; Liliana Inggrit Wijaya; Bertha Silvia Sutejo (Journal of Management and Business, 2015)
This study aims to examine the effect of short terms debt to total asset, long term debt to total asset , total debt to total asset, debt to equity ratio as a independent variables with sales growth and size as a control variable on infrastructure,utilities and transportation industry sector in Indonesia Stock Exchange (IDX) with the period 2010-2014. The variables tested are the variables that can affect profitability. This study uses a quantitative approach to multiple linear regression analysis model. This study used data drawn from infrastructure,utilities and transportation companies listed on Indonesia Stock Exchange for the period 2010-2014. The samples used in this study were 35 companies with 175 observation points at first by using classical. The study findings suggest that short term debt to total asset significant positive effect on the profitability, long term debt to total asset significant positive effect on the profitability, total debt to total asset significant positive effect on the profitability, debt to equity ratio is significantly negative effect on the use of profitability, size as a control variable contributed effect againsts independent variable against the dependent variable, sales growth as a control variable not contributed effect againsts independent variable against the dependent variable.